Unidirectional threshold switching induced by Cu migration with high selectivity and ultralow OFF current under gradual electroforming treatment - Dananjaya, Putu Andhita (2020)
A gradual electroforming process was implemented on the pristine Pt/HfOx/Cu/Pt structure to realize volatile threshold switching characteristics of a diffusive memristor. The reported devices exhibit stable unidirectional threshold switching properties with high selectivity of >107 and ultralow OFF current of ∼100 fA for over 104 endurance cycles. Nucleation theory on spheroidal-shaped metallic filament growth is used to extensively discuss the structural changes of the device after gradual forming treatments by analyzing the applied bias amplitude dependency of the finite delay time required by the device to turn ON under external electric field. On the other hand, the Rayleigh instability model was implemented for the aforementioned spheroidal metallic nucleus to explain the relaxation dynamics of the device. It was shown that the relaxation time of the device depends on the initial profile of the nucleus within the insulating layer. The broadening of the ON current distribution of the device was observed during the device endurance test. This is correlated to the presence of a random telegraph signal (RTS) during the ON state of the device.